Environmental and Welfare Effects of Large-Scale Integration of Renewables in the Electricity Sector - Daniel Davi-Arderius; Tooraj Jamasb; Juan Rosellon (Environmental and Resource Economics, 2024)
Abstract The 2022 energy crisis highlighted the dependence of the Europe electricity sector on imported natural gas and the need to accelerate the adoption of renewables to the power system. However, operating a reliable power system with high share of renewables might require curtailing some renewables and activating conventional generators not scheduled in the day-ahead markets to ensure system reliability. These actions can result in environmental impacts, higher system costs and welfare impacts for customers. We use a novel high-granularity data from the Spanish power system for the period 2019–2022 to estimate the effects of these actions and forecast future impact of implementing ambitious targets of the European Gas Reduction Plan. We show that reliance on conventional generators will sharply increase with the addition of renewables. However, higher electricity consumption reduces the negative welfare impacts of integrating renewables. Until renewables and storage technologies advance further, conventional generators are needed for reliable operation of the systems.
Additional information: L51;L94;Q41;Q42
Keywords: 330; Renewables; Decarbonization; Generation mix; Redispatching; Curtailment; Inverter-based resources; Synchronous generators; Day-ahead market; Network constraints; Gas crisis; System operator